Comparative population biology and reproduction of two sympatric crabs (Grapsidae) on Azores cobble beaches. Issue 3 (3rd July 2018) - Costa, Tarso De Menezes Macedo; Álvaro, Nuno Miguel da Silva Ascensão Vaz; Rodrigues, Armindo Dos Santos; Neto, Ana Isabel De Melo Azevedo; Azevedo, José Manuel Viegas Oliveira Neto
ABSTRACT: Population biology of the intertidal crabs Pachygrapsus marmoratus Fabricius, 1787 and P. maurus (Lucas 1846) was investigated at cobble beaches with different levels of wave exposure. Surveys were taken monthly over 1.5 years at three intertidal levels. The growth rate of both species was similar, although P. marmoratus reached larger sizes. This species was more abundant on the mid-littoral zone of sheltered beaches, whereas P. maurus was more abundant on more exposed ones. The sex ratio was male biased in both species, particularly for the smaller and larger size classes. Both species showed an extended reproductive season, coinciding with the rising temperatures of spring and summer, with ovigerous females being found from June to September for P. marmoratus and from May to August for P. maurus . The present study indicates that both could develop adaptive strategies allowing them to coexist in the Azores littoral. The greater size of P. marmoratus seems to be an advantage on the competition for refuges with P. maurus, which results in its higher abundance and general dominance in the higher shore levels and in less exposed shores. However, P. maurus seems to be more fitted to live in the higher hydrodynamic habitats.